Karyawan Milenial: Grit dan Prokrastinasi Kerja - Sagita Indah Pratama; Sowanya Ardi Prahara (Universitas Muhammadiyah Gresik, 2023)
Employees are important factor in the development of the company. Employees belonging to the millennial generation are prone to delaying behavior or work procrastination. The research aims to know if there's a link between grit with work procrastination on millenial workers. The research using quantitative method. The sampling technique using purposive technique. The sample of this research employs millenial workers (24 years old - 42 years old) with total of 72 workers. The instrument of this research employs grit scale and work procrastination scale. While the hypothesis of this research using spearman's rho correlation test. According the analysis' result, the Sig. (1-tailed) 0,014 < 0,050. Then, it is concluded that there's a significant link between grit with work procrastination. And then according to the coefficient number of correlation in the amount of -0,260, it means that the strength level of the link is low with the guidelines for the degree of relationship of 0,200-0,399. It is concluded that the higher the grit of someone get, the procrastination would be low. In reverse, a subject that has low grit level, the procrastination would be on higher level. The implication of this research is that there is a negative relationship between grit and work procrastination in millennial employees. Karyawan merupakan faktor penting dalam berkembangnya perusahaan. Karyawan yang tergolong generasi milenial rentan terhadap perilaku penundaan atau prokrastinasi kerja. Penelitian ini bertujuan untuk melihat apakah terdapat hubungan antara grit dengan prokrastinasi kerja pada karyawan milenial. Teknik sampling yang digunakan yaitu teknik purposive sampling. Sampel penelitian yang digunakan yaitu karyawan yang termasuk golongan usia milenial (24 tahun – 42 tahun) berjumlah 72 orang. Instrumen yang digunakan adalah Skala Grit dan Skala Prokrastinasi Kerja. Sedangkan untuk uji hipotesis menggunakan uji korelasi spearman’s rho. Berdasarkan hasil analisis didapatkan nilai sig. (1-tailed) 0,014 < 0,050 maka dapat dikatakan bahwa ada hubungan yang signifikan antara grit dengan prokrastinasi kerja. Sehingga dapat disimpulkan bahwa semakin tinggi grit yang dimiliki subjek, maka prokrastinasi akan semakin rendah. Sebaliknya, subjek yang memiliki grit rendah akan memiliki prokrastinasi yang tinggi. Implikasi pada penelitian ini adalah terdapat hubungan negatif antara grit dengan prokrastinasi kerja pada karyawan milenial.